Fraud Detection: Religion In The Workplace Big Data Analytics - Agus Bandiyono (Jurnal Akuntansi, 2023)
Researchers believe everyone wants to carry out religious teachings that are adhered to in the workplace, one of which is to act honestly. From an organizational point of view, big data analytics is used to suppress fraud which still occurs frequently, so this study aims to determine the effect of religion in the workplace and big data analytics on fraud detection. The research was conducted at Shariah People’s Credit Bank located in Banten Province, with a sample of 40 respondents. The data source was a questionnaire filled out by respondents. This study showed that religion in the workplace has a positive effect on fraud detection, and big data analytics has a positive effect on fraud detection. Further research is needed to test the variables of religion in the workplace and big data analytics.